O25-2 Central nervous system tumours and agricultural exposures in the prospective cohort agrican. (1st September 2016) - Piel, Clément; Pouchieu, Camille; Tual, Séverine; Migault, Lucile; Gruber, Anne; Berteaud, Emilie; Carles, Camille; Rondeau, Virginie; Lebailly, Pierre; Baldi, Isabelle
Abstract : Background: Studies in farmers suggest a possible role of pesticides in the occurrence of Central Nervous System (CNS) tumours. However, scientific evidences are still insufficient because of methodological limits such as study designs, sample sizes or exposure assessments. We aimed to study the associations between occupational exposures to a range of farming activities and the incidence of primary CNS tumours, globally and by subtiles. Methods: In the French prospective agricultural cohort AGRICAN, 181, 842 participants completed the enrollment questionnaire over the period 2005–2011. Associations between exposures to 13 crops and 5 livestock and the risks of CNS tumours (identified through linkage to cancer registries) were estimated using Cox models with age as underlying timescale, adjusted on gender, professional status and educational level. Effects of specific tasks, duration and periods of exposure were also assessed. Results: During a follow-up of 5.2 years in average, 273 incident cases of CNS tumours occurred, including 126 gliomas and 87 meningiomas. Analyses showed increased risks of CNS tumours that ranged from 10% to 85% with 11 of the 13 crops, significant in farmers growing peas and beets. Concerning gliomas, increases in risk were seen for all agricultural activities. A significant risk excess was observed in pesticide users (HR = 1.73; 95% CI: 1.05–2.84), especially in vine-growers performing treatments (HR = 1.86; 95% CI: 1.06–3.26). For meningiomas, significant positive associations were observed in sunflower growers, beet growers and hog raisers. A three-fold increased risk was seen in farmers using pesticides on potatoes (HR = 2.93; 95% CI: 1.15–7.47). Conclusion: In the largest prospective agricultural cohort, we observed increased risks of CNS tumours among farmers. Even if we cannot completely rule out the contribution of other agricultural factors, pesticide exposures are our main hypothesis to explain these findings. Further analyses will explore the effects of some specific pesticides using the crop-exposure matrix PESTIMAT.